Prediction of nonresectability using the updated Predictive Index value model assessed by imaging and surgery in tubo-ovarian cancer: a prospective multicenter ISAAC study - Moro, Francesca; Pinto, Patrícia; Chiappa, Valentina; Testa, Antonia Carla; Alcázar, Juan Luis; Franchi, Dorella; Benesova, Klára; Jarkovsky, Jiri; Frühauf, Filip; Borčinová, Martina; Burgetova, Andrea; Masek, Martin; et al. (American journal of obstetrics and gynecology, 2024)
BACKGROUND: A laparoscopy-based scoring system was developed by Fagotti et al (Fagotti or Predictive Index value (PIV)score) based on the intraoperative presence or absence of carcinomatosis on predefined sites. Later, the authors updated the PIV score calculated only in the absence of one or both absolute criteria of nonresectability (mesenteric retraction and miliary carcinomatosis of the small bowel) (updated PIV model). OBJECTIVE: The aim was to demonstrate the noninferiority of ultrasound to other imaging methods (contrast enhanced computed tomography (CT) and whole-body diffusion-weighted magnetic resonance imaging (WB-DWI)/MRI) in predicting nonresectable tumor (defined as residual disease >1 cm) using the updated PIV model in patients with tubo-ovarian cancer. The agreement between imaging and intraoperative findings as a reference was also calculated. STUDY DESIGN: This was a European prospective multicenter observational study. We included patients with suspected tubo-ovarian carcinoma who underwent preoperative staging and prediction of nonresectability at ultrasound, CT, WB-DWI/MRI, and surgical exploration. Ultrasound and CT were mandatory index tests, while WB-DWI/MRI was an optional test (non-available in all centers). The predictors of nonresectability were suspicious mesenteric retraction and/or miliary carcinomatosis of the small bowel or if absent, a PIV >8 (updated PIV model). The PIV score ranges from 0 to 12 according to the presence of disease in 6 predefined intra-abdominal sites (great omentum, liver surface, lesser omentum/stomach/spleen, parietal peritoneum, diaphragms, bowel serosa/mesentery). The reference standard was surgical outcome, in terms of residual disease >1 cm, assessed by laparoscopy and/or laparotomy. The area under the receiver operating characteristic curve (AUC) to assess the performance of the methods in predicting nonresectability was reported. Concordance between index tests at the detection of disease at 6 predefined sites and intraoperative exploration as reference standard was also calculated using Cohen's kappa. RESULTS: The study was between 2018 and 2022 in 5 European gynecological oncology centers. Data from 242 patients having both mandatory index tests (ultrasound and CT) were analyzed. 145/242 (59.9%) patients had no macroscopic residual tumor after surgery (R0) (5/145 laparoscopy and 140/145 laparotomy) and 17/242 (7.0%) had residual tumor ≤1 cm (R1) (laparotomy). In 80/242 patients (33.1%), the residual tumor was>1 cm (R2), 30 of them underwent laparotomy and maximum surgery was carried out, and 50/80 underwent laparoscopy only, because cytoreduction was not feasible in all of them. After excluding 18/242 (7.4%) patients operated on but not eligible for extensive surgery, the predictive performance of 3 imaging methods was analyzed in 167 women. The AUCs of all methods in discriminating between resectable and nonresectable tumor was 0.80 for ultrasound, 0.76 for CT, 0.71 for WB-DWI/MRI, and 0.90 for surgical exploration. Ultrasound had the highest agreement (Cohen's kappa ranging from 0.59 to 0.79) than CT and WB-DWI/MRI to assess all parameters included in the updated PIV model. CONCLUSION: Ultrasound showed noninferiority to CT and to WB-DWI/MRI in discriminating between resectable and nonresectable tumor using the updated PIV model. Ultrasound had the best agreement between imaging and intraoperative findings in the assessment of parameters included in the updated PIV model. Ultrasound is an acceptable method to assess abdominal disease and predict nonresectability in patients with tubo-ovarian cancer in the hands of specially trained ultrasound examiners.
Keywords: Neoplasm Staging; Ultrasonography; lidé středního věku; senioři; Diffusion Magnetic Resonance Imaging; Female; Humans; dospělí; computed tomography; magnetic resonance; laparoskopie; staging; Aged; ženské pohlaví; difuzní magnetická rezonance; Middle Aged; Predictive Value of Tests; laparotomy; lidé; ovarian cancer; počítačová rentgenová tomografie; reziduální nádor; Prospective Studies; Ovarian Neoplasms; Laparoscopy; prospektivní studie; ultrasonography; Tomography, X-Ray Computed; nádory vaječníků; ultrasonografie; laparoscopy; Adult; prediktivní hodnota testů; Neoplasm, Residual; staging nádorů